An Examination of Factors Associated With Self-Efficacy for Food Choice and Healthy Eating among Low-Income Adolescents in Three U.S. States - Muturi, Nancy W.; Kidd, Tandalayo; Khan, Tazrin; Kattelmann, Kendra; Zies, Susan; Lindshield, Erika; Adhikari, Koushik (Frontiers in Communication, 2016)
Background: Self-efficacy is a crucial component in effective health communication and health promotion interventions and serves as a moderator for behavior change. Although awareness and risk perception are important in the behavior change process, self-efficacy gives people the necessary confidence in their ability to engage in advocated health behaviors. In addressing childhood obesity, self-efficacy plays a crucial role in dietary decisions. Informed by the social cognitive theory, this study examines the behavioral and environmental factors that determine self-efficacy for healthy food choices and healthy eating among adolescents in low income communities. Method: A survey was administered among adolescents in 6th to 8th grades from three U.S. States – Kansas, Ohio and South Dakota (N=410). Results: Results show a correlation between efficacy for healthy food choice and the adolescent’s perceptions of behavioral control or sense of empowerment. Attitudes towards overall health predict efficacy for healthy eating and for healthy food choice. Other predictors for healthy eating include perceptions of peers’ health concerns and perceptions on healthy food availability whereas perceived control influences efficacy for healthy food choice. Gender played a significant role in adolescents’ perceptions of peers’ health concerns whereas geographical location (state played a role in their in adolescents’ attitudes toward health. Ethnicity was a more significant factor in their perceived barriers for healthy eating, perceptions for healthy food availability and in attitudes towards health. Conclusion: The study suggests ethnic-specific nutrition education that focuses on attitudes towards health as well as community partnerships that would support a healthy food environment to enhance self-efficacy and healthy dietary behaviors among adolescents.